Drifting Through Life - Collins, Deborah (Homœopathic Links, 2014)
The case of a young woman who drifted into drugs and prostitution, escaping from a difficult childhood, but subsequently found herself used by her surroundings. The remedy was given for her tendency to impulsiveness and instability (Lithium), as well as her tendency to drugs and prostitution (Fluoratum). Several doses of the remedy over time contributed to finding stability and grounding in her life, and helped her to stay away from further drug use.
Keywords: Drug abuse; Ungrounded; Impulsive; Prostitution; Lithium fluoratum